2019
DOI: 10.1016/j.drugalcdep.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of opioid misuse and opioid use disorder among primary care patients who use tobacco

Abstract: Background: Current data suggest that opioid misuse or opioid use disorder (OUD) may be over represented among tobacco users. However, this association remains understudied in primary care settings. A better understanding of the extent of heterogeneity in opioid misuse among primary care patients who use tobacco may have implications for improved primary care-based screening, prevention, and intervention approaches. Methods: Data were derived from a sample of 2,000 adult (aged ≥18) primary care patients acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Other substance dependence or abuse has been associated with opioid misuse based on varying risk factors. [13,28,33,47,50] In this study, we speci cally found that nicotine, [28,29] alcohol, [28,30] cocaine, [50] methamphetamine, [32] tranquilizers, [34,35,51] other illicit stimulants [20], and marijuana [28] have a positive relationship with opioid misuse and use disorder. The stimulant effect from nicotine, cocaine, methamphetamine, and other illicit stimulants have been stipulated to mitigate the depressive effects of opioids and may increase the "high" effect.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Other substance dependence or abuse has been associated with opioid misuse based on varying risk factors. [13,28,33,47,50] In this study, we speci cally found that nicotine, [28,29] alcohol, [28,30] cocaine, [50] methamphetamine, [32] tranquilizers, [34,35,51] other illicit stimulants [20], and marijuana [28] have a positive relationship with opioid misuse and use disorder. The stimulant effect from nicotine, cocaine, methamphetamine, and other illicit stimulants have been stipulated to mitigate the depressive effects of opioids and may increase the "high" effect.…”
Section: Discussionmentioning
confidence: 62%
“…The role of other substance dependence, abuse, and/or misuse, whether legal, illicit, or prescribed, has also been linked to opioid misuse and/or use disorder. Concurrent substance use such as nicotine and tobacco dependence [28,29], alcohol [30], sedatives [31], methamphetamines [32], tranquilizers [33][34][35], other analgesics [36], and marijuana [37] have been positively associated with opioid misuse and use disorder [37,38]. Marijuana may be context dependent as it has a mixed relationship with opioid use, misuse, and use disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Other substance dependence or abuse has been associated with opioid misuse based on various risk factors. [11,25,30,45,52] In this study, we found that nicotine [25,26], alcohol [25,27], cocaine [52], methamphetamine [29], tranquilizers [31,32,53], other illicit stimulants [15], and marijuana [25] have a positive relationship with opioid misuse and use disorder. The stimulant effect from nicotine, cocaine, methamphetamine, and other illicit stimulants may mitigate the depressive effects of opioids and may increase the "high" effect.…”
Section: Discussionmentioning
confidence: 63%
“…Concurrent substance use such as nicotine and tobacco dependence [25,26], alcohol [27], sedatives [28], methamphetamines [29], tranquilizers [30][31][32], other analgesics [33], and marijuana [34] have been positively associated with opioid misuse and use disorder [34,35]. Marijuana's association may be context dependent, as it has a mixed relationship with opioid use, misuse, and use disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Other substance dependence or abuse has been associated with opioid misuse based on varying risk factors. 19, 25−28 In this study, we specifically found that nicotine, 25,29 marijuana, 25 cocaine, 28 methamphetamine, 30 tranquilizers, 31−33 and stimulants 34 increase the probability toward opioid misuse. Although the present study revealed an increased association of opioid misuse with marijuana compared to non-marijuana users, the relationship in the literature has been mixed.…”
Section: Discussionmentioning
confidence: 74%